Answer:
1. No solution
2. Infinitely many solutions
3. Infinitely many solutions
4. One solution
Explanation:
1.
x=y-3
2x-2y=6
Substitute x=y-3 in (2)
2(y-3)-2y=6
2y-6-2y=6
2y-2y=6+6
0=12
No solution
2.
5x+2y=-7
10x+4y=-14
Multiply (1) by 2 and (2) by 1
10x+4y=-14
10x+4y=-14
Subtract (3) from (4)
0+0=0
0=0
Infinitely many solutions
3.
y=2x+1
4x-2y=-2
Substitute y=2x+1 into (2)
4x-2(2x+1)=-2
4x-4x-2=-2
4x-4x=-2+2
0=0
Infinitely many solutions
4.
9x+6y=15
2y= -1+3x
From 2
2y+1-3x=0
-3x+2y=-1
9x+6y=15 (1)
-3x+2y=-1 (2)
Multiply (2) by 3
-9x+6y=-3
9x+6y=15
Subtract (3) from (1)
9x-(-9x)=15-(-3)
9x+9x=15+3
18x=18
x=18/18
=1
x=1
Substitute x=1 into (1)
9x+6y=15
9(1)+6y=15
9+6y=15
6y=15-9
6y=6
y=6/6
=1
One solution